Spatial distribution of public health care facilities inrural areas of Nalanda district, Bihar - Kumar, Anand; Sharma, Dhiraj Kumar; Prakash, Satya; Yadava, R.S. (National Geographical Journal of India, 2022)
At this critical juncture of time when the whole world is facing a health care emergency due to the occurrence of (SARS-CoV-2) pandemic. It becomes necessary to critically evaluate public health care facilities and their availability to common people to tackle the ongoing crisis rationally. In this regard, this paper tries to study the spatial distribution of public health care facilities and their availability in rural areas of Nalanda district. Location quotient, Lorenz curve and Gini’s coefcient have been worked out to nd unequal concentration, availability and distribution of public health care facilities across the study area. To show the concentration and distribution of health care facilities over space maps have been drawn on ArcGIS. MS Excel and Word have been used for showing the availability of health care facilities through graphical representation and for tabulation purposes. This paper concludes that community development blocks surroundingdistrict headquarter havea higher concentration and larger availability ofrural public health care facilities in comparison to peripheral community development blocks of the study area.